Enhancing educational metadata with science education information - Sampson, Demetrios; Zervas, P. (2008)
During the past years a large amount of science education digital content became available worldwide in the form of science museum collections, digital repositories and libraries. An important factor, in order to make search and retrieval of science education content more efficient is the quality and quantity of educational metadata. Although the IEEE LOM Standard is used for describing educational resources with metadata, it beyond its scope to directly support the description of science curriculum related characteristics. In this paper we target addressing this issue, that is, to propose an IEEE LOM Science Education Application Profile that can be used for tagging science education resources. © 2008 IEEE.